LITERASI DAN INKLUSI KEUANGAN SYARIAH TERHADAP KEPUTUSAN INVESTASI DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERASI - Suryakusuma Kholid Hidayatullah; Siti Puryandani (Jurnal AKTUAL, 2022)
This study aims to analyze the factors that can influence investment decisions that are influenced by the level of Islamic financial literacy and Islamic financial inclusion moderated by locus of control. This study uses assessment indicators that are sourced from customer respondents in Pemalang Syariah Mandiri Bank which generally can be known qualitative data. In general, there are several factors that can influence the investment decisions of independent Islamic bank customers. In this study will emphasize the assessment of factors that can influence investment decisions in terms of literacy level, Islamic financial inclusion and locus of control of customers of Bank Syariah Mandiri, Pemalang Regency. The object of this research is an independent Islamic bank in Pemalang Regency. Data needs were obtained from the results of the customer questionnaire at Bank Syariah Mandiri Pemalang Regency. The analytical tool used in this research is the method of data analysis and partial hypothesis testing.